2002
DOI: 10.1007/s00264-002-0358-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary bipolar hemiprosthesis for unstable intertrochanteric fractures

Abstract: Between 1997 and 2001 we treated 54 elderly patients with unstable intertrochanteric fractures by primary hemiarthroplasty using a cemented bipolar prosthesis. Mean patient age was 75.6 (64-91) years and mean follow-up was 22.3 (5-48) months. Seven patients died before the fourth post-operative month. Thirty-three patients were able to walk with a walker in the first postoperative week. There were no dislocations or aseptic loosening. One deep infection was encountered after 1 year. Acetabular erosion was seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 18 publications
(18 reference statements)
7
95
1
4
Order By: Relevance
“…Rodop et al [14] reported the results of 37 patients with unstable intertrochanteric femoral fractures, who underwent cemented, bipolar hemiarthroplasty, were followedup for 12 months, and 80% of whom obtained excellent and good results using the Harris hip-scoring system. Furthermore, in a study by Tang et al, [10] Harris hip scores were 83 and 80.2 in PFNA and hemiarthroplasty groups, respectively, with no statistically significant difference between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Rodop et al [14] reported the results of 37 patients with unstable intertrochanteric femoral fractures, who underwent cemented, bipolar hemiarthroplasty, were followedup for 12 months, and 80% of whom obtained excellent and good results using the Harris hip-scoring system. Furthermore, in a study by Tang et al, [10] Harris hip scores were 83 and 80.2 in PFNA and hemiarthroplasty groups, respectively, with no statistically significant difference between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Classifications of these fractures are unreliable and therefore not useful in determining treatments. In general, fractures with comminution of the posteromedial cortex and subtrochanteric extension hemiarthroplasty were reported individually, [2,[10][11][12] to our knowledge, there has been no study comparing cemented and cementless hemiarthroplasty for intertrochanteric femur fractures in elderly patients. In the present study, we aimed to compare the reliability of cementless and cemented hemiarthroplasty for unstable intertrochanteric femur fractures in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Poor bone quality, Excessive collapse, loss of fixation, and cut-out of the lag screw are the common problems of attempts to fix these fractures. Some surgeons have recommended prosthetic replacement in such fractures but this has not gained widespread support [4][5][6][7]. Present study is an attempt to evaluate the functional outcome of primary cemented bipolar hemiarthroplasty in unstable inter-trochanteric fractures in elderly patients.…”
Section: Introductionmentioning
confidence: 99%